2022
DOI: 10.1155/2022/3771299
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Concrescence of Mandibular Third Molar and Supernumerary Fourth Molar

Abstract: Concrescence reveals a rare developmental anomaly in which two fully formed teeth are joined along the root surfaces by cementum, and generally occurs in maxillary molars, especially in a third molar and a supernumerary tooth. Very few cases have been reported about the concrescence of a third molar and a supernumerary fourth molar. Based on our available knowledge, this case report described a rare presentation in which concrescence is observed between a third molar and a supernumerary fourth molar in the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…maxilla involving an impacted third molar and the second molar [5]. Wang J. et al reported a rare case of successful surgical division of 6 of 9 concrescent teeth [7]. A massive bone defect after extraction has been repaired by filling a space-occupying bone defect between a third molar and a supernumerary fourth molar with space-occupying bone-filling materials [7].…”
Section: Shilpa G (2013) [16] Case Report 5 Years/ Male Primary Denti...mentioning
confidence: 99%
“…maxilla involving an impacted third molar and the second molar [5]. Wang J. et al reported a rare case of successful surgical division of 6 of 9 concrescent teeth [7]. A massive bone defect after extraction has been repaired by filling a space-occupying bone defect between a third molar and a supernumerary fourth molar with space-occupying bone-filling materials [7].…”
Section: Shilpa G (2013) [16] Case Report 5 Years/ Male Primary Denti...mentioning
confidence: 99%